Dopamine Axon Targeting in the Nucleus Accumbens in Adolescence Requires Netrin-1 - Cuesta, Santiago; Nouel, Dominique; Reynolds, Lauren M.; Morgunova, Alice; Torres-Berrío, Angélica; White, Amanda; Hernandez, Giovanni; Cooper, Helen M.; Flores, Cecilia (Frontiers in Cell and Developmental Biology, 2020)
The fine arrangement of neuronal connectivity during development involves the coordinated action of guidance cues and their receptors. In adolescence, the dopamine circuitry is still developing, with mesolimbic dopamine axons undergoing target-recognition events in the nucleus accumbens, while mesocortical projections continue to grow towards the prefrontal cortex until adulthood. This segregation of mesolimbic versus mesocortical dopamine pathways is mediated by the guidance cue receptor DCC, which signals dopamine axons intended to innervate the nucleus accumbens to recognize this region as their final target. Whether DCC-dependent mesolimbic dopamine axon targeting in adolescence requires the action of its ligand, Netrin-1, is unknown. Here we combined shRNA strategies, quantitative analysis of pre- and post-synaptic markers of neuronal connectivity, and pharmacological manipulations to address this question. Similar to DCC levels in the ventral tegmental area, Netrin-1 expression in the nucleus accumbens is dynamic across postnatal life, transitioning from high to low expression across adolescence. Silencing Netrin-1 in the nucleus accumbens in adolescence results in an increase in the expanse of the dopamine input to the prefrontal cortex in adulthood, with a corresponding increase in the number of presynaptic dopamine sites. This manipulation also results in altered dendritic spine density and morphology of medium spiny neurons in the nucleus accumbens in adulthood and in reduced sensitivity to the behavioral activating effects of the stimulant drug of abuse, amphetamine. These cellular and behavioral effects mirror those induced by Dcc haploinsufficiency within dopamine neurons in adolescence. Dopamine targeting in adolescence requires the complementary interaction between DCC receptors in mesolimbic dopamine axons and Netrin-1 in the nucleus accumbens. Factors regulating either DCC or Netrin-1 in adolescence can disrupt mesocorticolimbic dopamine development, rendering vulnerability or protection to phenotypes associated with psychiatric disorders.